Positionen Hedendaagse Oostenrijkse Kunst : Museum Moderner Kunst Stiftung Ludwig Wien. - Bitterlich, Konrad; Fuchs, Rainer; Hegyi, Lóránd; Kowanz, Brigitte; Kuspit, Donald; Lachnit, Edwin; Lighart, Theo; Lippens, Leopold Graaf; Schlegel, Eva; Schmidt, H.W.; Schrage, Dieter; Spiegl, Andreas; et al. (Knokke-Heist : Cultureel Centrum Knokke-Heist vzw, 1998)
Appelt, Siegrun ; Brandl, Herbert ; Dunst, Heinrich ; Gasteiger, Jakob ; Graf, Franz ; Grubinger, Eva ; Hoeck, Richard ; Jürgenssen, Birgit ; Jocher, Thomas ; Kempinger, Herwig ; Kowanz, Brigitte ; Krawagna, Suse ; B., Ona ; Pichler, Franz ; Rainer, Helmut ; Ruhm, Constanze ; Schlegel, Eva ; Selichar, Günther ; Stanzel, Rudi ; Vopova, Walter ; Wakolbinger, Manfred ; Zimmer, Klaus Dieter ; Zitko, Otto ; Zogmayer, Leo
biografie
Positionen Hedendaagse Oostenrijkse Kunst : Museum Moderner Kunst Stiftung Ludwig Wien, Cultureel Centrum Knokke-Heist vzw, 17.7. - 6.9.1998
Nederlands
boek
Keywords: Oostenrijk